CREATINE KINASE MYOCARDIAL BAND, MYELOPEROXIDASE, MATRIX METALLOPROTEINASE-9 DAN TROPONIN T PADA IMA - IA Hutagalung; I Patellongi; R Pakasi; M Arif; AA Mappahya; Hardjoeno . (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2011)
In many patients presenting with chest pain symptoms at the emergency room, cardiac markers are measured not only to detect acutemyocardial infarction (AMI) but to exclude them too. Presently, the only biochemical markers used for diagnosis of MI are creatine kinasemyocardial band (CKMB) and troponin T (cTnT) as the markers of myocardial necrosis. Other biochemical markers have been sought tofind marker which can reflect the important, upstream processes in the pathophysiology of MI that therefore might give an earlier signalof ongoing MI. These markers are myeloperoxidase (MPO) and matrix metalloproteinase-9 (MMP-9) as markers of plaque destabilization.The aim of this study was to analyze the CKMB, MPO, MMP-9 activityies and troponin T level in MI. A cross sectional study had beendone at the Cardiovascular Centre Unit and Internal Ward of Dr. Wahidin Sudirohusodo Hospital during April up to August 2010 period.The laboratory tests were done at the Clinical Pathology Laboratory of Dr. Wahidin Sudirohusodo Hospital, Makassar and the Researchand Esoteric Unit of Prodia Clinical Laboratory, Jakarta. Ffifty-three patients with AMI had been examined. The results showed that themeans of CKMB, cTnT, MPO and MMP-9 were 52.4 U/L, 2.0 ng/mL, 217.9 ng/mL and 920.3 ng/mL, respectively. MMP-9 had positivelyvalue (69.8%) higher than cTnT (60.4%), MPO (58.5%) and CKMB (45.3%). Troponin T and MMP-9 were higher in patients with highCKMB. The higher level of CKMB will be the higher MPO, MMP-9 and cTnT. There were strong correlation between MPO and MMP-9, alsobetween CKMB and Troponin T. Troponin T and CKMB were lower in inferior wall infarction compared with anterolateral/anteroseptal wallinfarction. The most sensitive biochemical marker in patients with AMI is the MMP-9. The MMP-9 usage is suggested to assist the diagnosisof AMI. It is suggested a further study to establish the specificity of MMP-9 in all patients suffering with chest pain.